Partially Acidulation as an Alternative Means of Utilizing Phosphate Rocks of Different Origins in an Alkaline Calcareous Soil of Haryana, India - Nayan Ahmed; D.R. Biswas, B. Mhalla, R.D. Singh (Journal of the Indian Society of Soil Science, 2017)
Four phosphate rocks (PRs) of different origin namely, two from middle East viz., Syrian PR and Jordanian PR and two from India viz., Purulia PR and Udaipur PR were acidulated with sulphuric acid at 0, 25 and 50% levels of acidulation, in order to increase phosphorus (P) availability. The release pattern of P from partially acidulated PR (PAPRs) products were studied through an incubation experiment and their relative agronomic effectiveness (RAE) were tested in a greenhouse experiment with respect to single superphosphate (SSP) by wheat in an alkaline calcareous soil (pH 8.8). The acidulated products were analyzed for different P fractions i.e. total P, water soluble P (WSP), citrate soluble P (CSP) and citrate insoluble P (CISP). The results showed that with the increase in the degree of acidulation both total and CISP fractions deceased while WSP and CSP as a percentage of total P increased. The release of P increased significantly when the soil was treated with different PAPRs, as evident by higher available P (19.0 - 23.5 mg P kg-1 soil) over no-P (control) treatment (11.5 mg P kg-1 soil) during 90 days of incubation irrespective of P sources. In addition, P release increased with increasing the degree of acidulation. However, the mean value of released P from PAPRs was significantly inferior to SSP (32.0 mg P kg-1 soil). The results obtained from greenhouse study closely followed the pattern observed in the incubation study. Significant increase in yield and P uptake by wheat was noticed in treatments receiving with P-fertilizer as compared to unfertilized control. The maximum RAE value increased to 85%. Effectiveness of PRs as source of P to wheat followed the order of Jordanian PR > Syrian PR = Purulia PR > Udaipur PR. The post-harvest available P status in soil also followed similar trend. The present results demonstrated that PAPRs which save 50% of acid consumption compared to complete acidulation could be an alternative means of utilizing low-grade PRs from different origins as P-fertilizer in alkaline calcareous soil although it is slightly less effective (about 85% RAE values) than SSP.